The Effect of Transformational Leadership on Personnel Performance Through Work Discipline as A Mediating Variable at The Indonesian National Police Headquarters - Amin Amin; Mentiana Sibarani (Amkop Management Accounting Review (AMAR), 2026)
This study aims to examine the effect of transformational leadership on personnel performance, with work discipline as a mediating variable, among staff of the Personal Secretariat of the Indonesian National Police Headquarters. The study employs a quantitative approach with an explanatory research design. Data were collected using a structured questionnaire distributed to 135 personnel selected via simple random sampling. The data were analyzed using multiple linear regression, path analysis, and mediation testing to identify direct and indirect relationships among variables. The findings indicate that transformational leadership has a positive and significant effect on work discipline, while work discipline has a positive and significant effect on personnel performance. However, transformational leadership does not have a significant direct effect on personnel performance. Mediation analysis shows that work discipline significantly mediates the relationship between transformational leadership and personnel performance. These results suggest that transformational leadership contributes to performance improvement indirectly by strengthening work discipline. The originality of this study lies in highlighting the critical role of work discipline as a behavioral mechanism linking leadership style to performance outcomes within a highly structured public-sector organization. The findings provide empirical evidence that effective leadership must be supported by strong disciplinary practices to achieve optimal personnel performance.